Vanished : Stories - Lin-Greenberg, Karin (Book collections on Project MUSE., 2022)
"The stories in Vanished feature women and girls who are often overlooked or unseen. Each character is dealing with something or someone who has vanished--a person close to them, a friendship, a relationship--as they search to make sense of the world around them in the wake of what's been lost"--